TEACHER EMPOWERMENT IN APPLYING LEARNING PRINCIPLES TO DEAF STUDENTS IN ELEMENTARY SCHOOL, SUKAMAKMUR DISTRICT - Murni Winarsih; Totok Bintoro (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2018)
ABSTRACT The purpose of this community service activity is to provide knowledge and skills to elementary school teachers in applying the principles of learning for deaf students in inclusive education institutions. Insights into the knowledge and skills provided about the basic concepts of inclusive education, the introduction of ABK and its characteristics, identification of deaf ABK, the principles of deaf ABK learning and assessment of learning outcomes for deaf ABK. This activity was carried out in the form of Technical Guidance (Bimtek) for elementary school teachers. The topic was the Socialization of Children with Special Needs specifically Deafness in the Fostered area of Sukamakmur District, Bogor. This community service is carried out for 2 (two) days through training methods, lectures, interactive discussions, Q and A with speakers coming from lecturers of Special Education (PKh) study programs. This P2M activity was followed enthusiastically by 50 teachers from schools located in Sukamakmur District. The results obtained from this P2M activity are changes in the mindset of teachers in looking at ABK and addressing inclusive education. In addition, teachers also have skills in identifying deaf ABK and learning by using specific principles for deaf ABK. It is expected that this P2M activity can be continued in the following year with more diverse material and wider target groups. ABSTRAK Tujuan kegiatan pengabdian kepada masyarakat ini adalah untuk memberikan bekal pengetahuan dan keterampilan kepada guru sekolah dasar dalam menerapkan prinsip-prinsip pembelajaran untuk siswa tunarungu yang berada di sekolah penyelengagara pendidikan inklusif. Wawasan pengetahuan dan keterampilan yang diberikan tentang konsep dasar pendidikan inklusif, pengenalan ABK dan karakteristiknya, identifikasi ABK tunarungu, prinsip-prinsip pembelajaran ABK tunarungu dan penilaian hasil belajar bagi ABK tunarungu. Kegiatan ini dilakukan dalam bentuk Bimbingan Teknis (Bimtek) untuk guru sekolah dasar tentang Sosialisasi Anak Berkebutuhan Khusus Tunarungu Di Gugus Wilayah Binaan Kecamatan Sukamakmur Bogor. Pengabdian masyarakat ini dilaksanakan selama 2 (dua) hari dengan metode pelatihan, melalui ceramah, diskusi dan tanya jawab interaktif, dengan nara sumber yaitu dosen-dosen program studi Pendidikan Khusus (PKh). Kegiatan P2M ini diikuti dengan antusias dan penuh semangat oleh 50 orang guru yang berasal dari sekolah-sekolah yang berada di Kecamatan Sukamakmur. Hasil yang diperoleh dari kegiatan P2M ini adalah perubahan mindset para guru dalam memandang ABK dan menyikapi pendidikan inklusif. Selain itu guru-guru juga memiliki keterampilan dalam mengidentifikasi ABK tunarungu serta melakukan pembelajaran dengan menggunakan prinsip-prisip khusus bagi ABK tunarungu. Diharapkan kegiatan P2M ini dapat dilanjutkan pada tahun berikutnya dengan materi yang lebih beragam dan kelompok sasaran yang lebih luas lagi.